Day 3 Wed, November 09, 2016 2016
DOI: 10.2118/183101-ms
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices and Challenges for Pipeline Design and Construction in Populated Area

Abstract: Pipeline Design and Construction in populated areas to ensure Safety and Integrity of Pipeline System as well as Public Safety in the pipeline vicinity is a major challenge. GASCO is one of the largest gas processing companies in the world, and it is considered as the major energy and feedstock supplier for the majority of the power, hydrocarbon, and petrochemical industries based in the UAE. GASCO operates pipelines network having total length of approximately 3,500km, and suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Tey concluded that the geometry of the relief valve is crucial to its performance, such as the coaxially of the disk. Pipeline codes have complied with a selection of design factors, pipeline location, and maximum distance requirements between sectionalized gate valves [6]. Switching valves enable the piping systems to be turned on and of.…”
Section: Introductionmentioning
confidence: 99%
“…Tey concluded that the geometry of the relief valve is crucial to its performance, such as the coaxially of the disk. Pipeline codes have complied with a selection of design factors, pipeline location, and maximum distance requirements between sectionalized gate valves [6]. Switching valves enable the piping systems to be turned on and of.…”
Section: Introductionmentioning
confidence: 99%